A 'Queen' in the Band - Unknown (Daily Express)
This picture depicts "Miss Better Village" Olivia Doobay, admiring two young members of the Ideal Supply Store Steel Orchestra of Arima. The steelband will take part in competitions in the borough of Arima during the Carnival celebrations.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Carnival -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago